2008
DOI: 10.1093/humupd/dmn060
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin/kexin type 4 in mammalian fertility: a review

Abstract: PCSK4 appears to be a crucial enzyme for reproduction. Alterations of PCSK4 expression or activity could be the underlying cause of some unexplained cases of human infertility. Conversely, inactivation of this protease represents a potential strategy for non-hormonal contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 119 publications
4
25
0
Order By: Relevance
“…Further, PC2 together with PC1 generates insulin through endoproteolytic processing of preproinsulin (Bailyes et al, 1991; Seidah and Prat, 2012; Steiner et al, 1996). IGF-2 has been found to be processed by PC4 in other tissues (Qiu et al, 2005; Tani et al, 2008); in fact, this enzyme subtype is exclusively expressed in testicular germ cells in males and in the placenta and ovary in females (Gyamera-Acheampong and Mbikay, 2009; Seidah and Prat, 2012), and therefore it is unlikely that PC4 is responsible for IGF-2 processing in the brain. We suggest that in the brain PC2 and/or PC2 together with PC1 process precursor forms of IGF-2 into mature IGF-2, and identifying approaches that reduce PC2 deficits may also be an interesting and novel avenue for developing therapies against cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Further, PC2 together with PC1 generates insulin through endoproteolytic processing of preproinsulin (Bailyes et al, 1991; Seidah and Prat, 2012; Steiner et al, 1996). IGF-2 has been found to be processed by PC4 in other tissues (Qiu et al, 2005; Tani et al, 2008); in fact, this enzyme subtype is exclusively expressed in testicular germ cells in males and in the placenta and ovary in females (Gyamera-Acheampong and Mbikay, 2009; Seidah and Prat, 2012), and therefore it is unlikely that PC4 is responsible for IGF-2 processing in the brain. We suggest that in the brain PC2 and/or PC2 together with PC1 process precursor forms of IGF-2 into mature IGF-2, and identifying approaches that reduce PC2 deficits may also be an interesting and novel avenue for developing therapies against cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Our pharmacological experiments showed that PMSF and furin inhibitors (Dec-RVKR-CMK and hexa-Darginine) inhibited the activation of PLB during sterol removal, whereas benzamidine, trypsin inhibitor, and leupeptin did not. Furin belongs to the proprotein convertase subtilisin/kexin type (PCSK) family consisting of nine serine endoproteases (55). Studies with transcriptome analysis and immunolocalization identified that PCSK3 (furin), PCSK4, and PCSK7 (56 -58) are expressed in the testis.…”
Section: Discussionmentioning
confidence: 99%
“…Pc4 2/2 mice do not show any altered spermatogenesis, but spermatozoa exhibit accelerated capacitation, precocious acrosome reaction, and reduced spermatozoa-egg binding ability that is only half that of wild-type mice. Eggs fertilized by these sperm fail to grow to the blastocyst stage (Gyamera-Acheampong and Mbikay, 2009;Gyamera-Acheampong et al, 2006;Mbikay et al, 1997).…”
Section: Microscopy Research and Techniquementioning
confidence: 99%